Internet addiction: the Czech and Slovak adolescent population - Kňažek, Gabriel; Považanová, Barbora Kňažek; Dolejš, Martin (BMC psychology, 2024)
BACKGROUND: Adolescence is often seen as an important period for further personality development. In today's world, it is therefore important to keep track of current trends in adolescents. One of them is addictive behaviour in the context of the online environment. Spending too much time online can have a negative impact on the quality of life of adolescents. It is therefore important to pay increased attention to this phenomenon and to respond adequately to the current situation. METHODS: Our study focuses on the prevalence of Internet addiction among Czech and Slovak adolescents. In total, 3,741 respondents participated in the project (N = 2,642 CZ; N = 1,099 SK); their ages ranged from 11 to 19 years (M = 14.38; SD ± 2.27). The research addressed differences among individual types of schools and between sexes in relation to Internet addiction. The research focused on adolescents attending secondary schools (ISCED 2 and 3) between the ages of 11 and 19 in the Czech and Slovak Republics. A questionnaire battery consisting of a sociodemographic questionnaire and the Internet Addiction Test (IAT) questionnaire was used for data collection. RESULTS: In relation to the category of Internet use, girls did not score higher than boys either in the Czech group F(1, 2112) = .089, p = .765, or in the Slovak group F(1, 927) < .001 p = .994. There is a significant effect of school type both in the Czech group F(4, 2100) = 11.483, p < .001, and in the Slovak group F(4, 859) = 2.859, p = .023. CONCLUSIONS: Our research indicates that some adolescents, particularly boys, face issues with excessive Internet use, affecting social interactions. Further studies in the Czech Republic could explore the link between psychosocial factors and adolescent Internet use. This highlights the need to raise awareness among professionals about Internet addiction in Czech and Slovak adolescents.
Keywords: Male; Adolescent Behavior; Prevalence; Slovenská republika; návykové chování; Sex Factors; Surveys and Questionnaires; netholismus; Humans; Internet Addiction Disorder; Internet addiction; Czech Republic; Česká republika; mužské pohlaví; prevalence; Female; mladiství; Behavior, Addictive; chování mladistvých; ženské pohlaví; průzkumy a dotazníky; internet; mladý dospělý; Young Adult; Adolescents; IAT; sexuální faktory; Slovakia; Internet; Adolescent; lidé; dítě; Child; School